Enhancing business resilience: Innovation and adaptation during and after the global pandemic - Nosike, Chukwunonso Joseph; Ojobor, Oluchukwu Sandra Nosike; Nosike, Cynthia Uju (International Journal of Financial, Accounting, and Management, 2024)
Purpose: In response to the unprecedented challenges posed by the global pandemic, this study rigorously examines the strategic interplay between innovation and adaptation as catalysts for business resilience. Method: The research investigates the influence of two independent variables – innovation in business and adaptive strategies – on the dependent variable of business resilience, establishing a robust conceptual framework based on a thorough literature review. Employing a mixed-methods approach, incorporating case studies, surveys, and interviews, the study meticulously explores the multifaceted dimensions of business responses during the pandemic. Results: A detailed analysis of innovation encompasses technological, process, and product innovations, while simultaneously scrutinizing adaptive strategies such as flexible business models, employee empowerment, and customer-centric approaches. The research reveals that businesses embracing process and technological innovation alongside radical shifts in their business models achieved higher levels of resilience. Qualitative narratives assess the performance metrics and success stories of these resilient businesses. The examination extends to the post-pandemic landscape, evaluating the sustainability of innovation and adaptation in a stable environment. Emphasis is placed on the enduring relevance of these strategies and their integration into organizational culture, thereby shaping long-term business resilience. Limitations: The study identifies and addresses challenges and barriers hindering innovation and adaptation, including economic constraints, technological barriers, and organizational resistance.   Contribution:  This study offers a nuanced and insightful exploration of the intricate dynamics between innovation, adaptation, and business resilience during and after the pandemic. The findings not only contribute to the academic discourse but also provide actionable insights for businesses seeking to fortify their resilience amidst ongoing global uncertainties.